A selective arsenic depressant composition for copper-arsenic flotation separation and its use

CN122895121APending Publication Date: 2026-10-13TIBET JINLONG MINING CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611351634.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明目的之一在于提供一种用于铜砷浮选分离的选择性抑砷剂组合物,以解决现有技术中抑砷剂选择性不足、在抑制含砷矿物的同时使铜回收率显著下降,以及依赖高碱工艺的问题

Benefits of technology

[0028]1、本发明将抑砷与保铜相互解耦,通过以亚硫酸盐与氧化诱导剂构成氧化还原缓冲对,把矿浆电位钳制在含砷矿物表面氧化起始电位以上,铜矿物深度氧化电位以下的窄窗口内,从而使抑砷与保铜由此前的单调权衡关系转为可以分别调控的两件事,使得本发明使铜精矿砷品位相对降低43.06%,而铜回收率的相对损失仅为1.86%,铜精矿品位则同步提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122895121A_ABST
    Figure CN122895121A_ABST
Patent Text Reader

Abstract

The application discloses a selective arsenic inhibitor composition for copper-arsenic flotation separation and application thereof, and belongs to the technical field of mineral flotation reagents. The composition comprises 30-50 parts by weight of a multifunctional high-molecular inhibitor, 20-40 parts by weight of a sulfite and 5-15 parts by weight of an oxidation inducer, wherein the multifunctional high-molecular inhibitor is a water-soluble high-molecular polymer with a number average molecular weight of 5000-20000 and containing carboxyl, mercapto and phenolic hydroxyl groups in the same molecular chain. The application uses a redox buffer pair composed of the sulfite and the oxidation inducer to clamp the pulp potential in a narrow window, so that the surface of the arsenic-containing mineral is directionally oxidized to form high-density sites and is anchored by the inhibitor to form a hydrophilic film, and the surface of the copper mineral only forms weak adsorption, thereby relatively reducing the arsenic grade of the copper concentrate by 43.06% under the medium alkaline condition, and relatively losing the copper recovery rate by only 1.86%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mineral flotation reagents, and more particularly to a selective arsenic inhibitor composition for copper-arsenic flotation separation, a copper-arsenic flotation separation method, and the application of the composition. Background Technology

[0002] In the flotation process of copper sulfide ores, arsenic removal is crucial to ensuring the quality of copper concentrate. Common arsenic-bearing minerals include arsenopyrite, arsenic chalcopyrite, and arsenic sulfide. These minerals have similar floatability to copper minerals such as chalcopyrite and chalcocite, making them difficult to separate.

[0003] Existing arsenic suppression methods typically employ inorganic arsenic inhibitors, primarily sodium sulfite or sodium metabisulfite, supplemented with water glass dispersion. This method involves adding sulfite to a moderately alkaline slurry, relying on the reducing effect of sulfite ions to lower the slurry potential and complex with heavy metal ions on the mineral surface, making it difficult for arsenic-containing minerals to form a hydrophobic film. However, sulfite is a purely reducing agent, and the low-oxidation surface it maintains lacks high-valence oxygen-containing sites that can firmly bond with the inhibitor. The inhibitor can only be loosely adsorbed via electrostatics and weak hydrogen bonds, resulting in a non-dense film. Simultaneously, sulfite ions are small molecules, and the surface area covered by each adsorption site is extremely small, failing to form a continuous hydrophilic coating. The inhibitory effect is highly dependent on continuous excessive addition. Furthermore, this method indiscriminately reduces the surface oxidation level of all sulfide minerals, weakening the floatability of copper minerals while suppressing arsenic. In addition, there are methods using small-molecule organic inhibitors such as mercaptoacetic acid. The thiol groups in these reagents can coordinate with arsenic and iron sites on the surface of arsenic-containing minerals, resulting in a reasonable arsenic inhibition effect. However, the thiol groups have a stronger affinity for monovalent copper sites on the surface of chalcocite, inhibiting easily oxidized copper minerals along with arsenic-containing minerals, leading to a significant decrease in copper recovery. Because these reagents have only a single type of functional group on their molecules, they can only form monodentate adsorption. The difference in adsorption intensity between arsenic-containing minerals and copper minerals remains limited. This lack of selectivity is an inherent defect in their principle and cannot be overcome by adjusting the dosage.

[0004] Therefore, existing technologies suffer from problems such as insufficient selectivity of arsenic inhibitors, excessive loss of copper recovery rate while reducing the arsenic grade of copper concentrate to the target level, or a series of process and environmental burdens due to reliance on high-alkali processes. Summary of the Invention

[0005] One of the objectives of this invention is to provide a selective arsenic suppressant composition for copper-arsenic flotation separation, in order to solve the problems of insufficient selectivity of arsenic suppressants in the prior art, significant decrease in copper recovery rate while suppressing arsenic-containing minerals, and dependence on high-alkali processes.

[0006] This invention is achieved through the following technical solution:

[0007] A selective arsenic inhibitor composition for copper-arsenic flotation separation, the selective arsenic inhibitor composition comprising the following components in parts by weight: 30-50 parts of a multifunctional polymeric inhibitor, 20-40 parts of a sulfite, and 5-15 parts of an oxidation inducer; wherein the multifunctional polymeric inhibitor is a water-soluble polymer containing carboxyl, thiol, and phenolic hydroxyl groups on the same molecular chain, and the number average molecular weight of the multifunctional polymeric inhibitor is 5000-20000.

[0008] Furthermore, the weight ratio of the sulfite to the oxidation inducer is 2:1 to 6:1.

[0009] Furthermore, the selective arsenic inhibitor composition further includes 5 to 10 parts by weight of a dispersant.

[0010] Furthermore, in the multifunctional polymeric inhibitor, the carboxyl group content is 2.0~6.0 mmol / g, the thiol group content is 0.3~1.5 mmol / g, and the phenolic hydroxyl group content is 0.5~3.0 mmol / g.

[0011] Furthermore, the sulfite is at least one of sodium sulfite and sodium metabisulfite.

[0012] Furthermore, the oxidation inducer is at least one of persulfate, percarbonate, and permanganate.

[0013] Furthermore, the dispersant is at least one of water glass and sodium hexametaphosphate.

[0014] Furthermore, the selective arsenic inhibitor composition comprises the multifunctional polymeric inhibitor, the sulfite, the oxidation inducer, and the dispersant; based on the total weight of the selective arsenic inhibitor composition, the content of the multifunctional polymeric inhibitor is 30%~50%, the content of the sulfite is 20%~40%, the content of the oxidation inducer is 5%~15%, the content of the dispersant is 5%~10%, and the sum of the weight percentages of the above four components is 100%.

[0015] Furthermore, the multifunctional polymer inhibitor is a modified product obtained by chain extension, esterification to introduce carboxyl groups and esterification to introduce thiol groups from natural polyphenols, or a grafted product obtained by amidation grafting of thiol-containing units and phenolic hydroxyl-containing units from polycarboxylic acids.

[0016] Furthermore, the selective arsenic inhibitor composition is a solid powder formed by pre-mixing the components, or a packaged formulation in which the sulfite and the oxidation inducer are packaged separately and added to the slurry simultaneously during use.

[0017] Another aspect of the present invention provides a method for copper-arsenic flotation separation, the method comprising the following steps: a. grinding arsenic-containing copper ore and preparing it into a slurry; b. adjusting the pH value of the slurry to 8.5-11.0; c. adding the above-mentioned selective arsenic inhibitor composition to the slurry and stirring to activate it, so that the slurry potential falls into a set range and a hydrophilic film is formed on the surface of the arsenic-containing minerals in the arsenic-containing copper ore; d. adding a collector and a frother to the slurry treated in step c and performing flotation to obtain copper concentrate and tailings.

[0018] Furthermore, in step a, the fineness of the grinding is -200 mesh, accounting for 70% to 85%.

[0019] Furthermore, in step b, the pH value of the slurry is 9.0~11.0.

[0020] Further, in step c, the amount of the selective arsenic inhibitor composition is 200~600g / t.

[0021] Furthermore, in step c, the stirring activation time is 2 to 8 minutes.

[0022] Further, in step c, the set range is +50 to +250 mV relative to the standard hydrogen electrode.

[0023] Further, in step d, the collector is at least one of xanthate collectors, nitric acid collectors, and 2025A.

[0024] Further, in step c, the sulfite and the oxidation inducer in the selective arsenic inhibitor composition are respectively added to the slurry.

[0025] The present invention also provides the application of the above-mentioned selective arsenic inhibitor composition in the flotation separation of copper minerals and arsenic-containing minerals in arsenic-containing copper ore.

[0026] Furthermore, the arsenic-containing mineral is at least one of arsenopyrite, arsenic chalcopyrite, and thioarsenic chalcopyrite, and the copper mineral is at least one of chalcopyrite and chalcocite.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] 1. This invention decouples arsenic suppression and copper preservation. By using sulfite and oxidation inducer to form a redox buffer pair, the slurry potential is clamped within a narrow window above the oxidation initiation potential of arsenic-containing minerals and below the deep oxidation potential of copper minerals. This transforms the previous monotonic trade-off between arsenic suppression and copper preservation into two separately controllable processes. As a result, this invention reduces the arsenic grade of copper concentrate by 43.06%, while the relative loss in copper recovery is only 1.86%, and the copper concentrate grade is simultaneously improved.

[0029] 2. The three components of this invention interact synergistically rather than simply additively. The multifunctional polymeric inhibitor is responsible for film formation, the oxidation inducer is responsible for inducing active sites on the surface of arsenic-containing minerals, and the sulfite is responsible for clamping the slurry potential within a window. Their functions do not overlap, and the absence of any one component cannot be compensated for by the others. In a comparison using the same conditions and total dosage, the complete formulation outperforms the control group (without all single components) in both arsenic grade and copper recovery in copper concentrate.

[0030] 3. The present invention has a large selectivity margin. Within the pH range of 9.0 to 11.0, after adding the composition of the present invention, the difference between the lowest recovery rate of the two copper minerals and the highest recovery rate of the two arsenic-containing minerals is always greater than 63.0 percentage points; while under the same conditions, the difference corresponding to small molecule thiol inhibitors is always negative.

[0031] 4. The slurry potential of this invention can be stably clamped. During the stirring and activation period of 2-8 minutes, the slurry potential corresponding to the composition of this invention fluctuates only between 214.0 and 221.0 mV, with a bandwidth of only 7.0 mV, and always falls within the window. In contrast, the control with only oxidation inducer has a slurry potential of no less than 322.0 mV in the same range, and the control with only sulfite has a slurry potential of no more than 42.0 mV, both of which are outside the window. When the weight ratio of sulfite to oxidation inducer decreases to 1:1, the slurry potential rises to 289.0 mV and exceeds the upper limit of the window, and the copper recovery rate drops to 85.9%, indicating that this ratio is a key parameter that determines the potential drop point and thus the copper retention effect.

[0032] 5. The process conditions of this invention are mild, and the alkali consumption and process burden are significantly reduced. The effective window of this invention is between pH 8.5 and 11.0. Within this range, the arsenic grade of the crude concentrate is not higher than 0.55% and the copper recovery rate is not lower than 91.5%. There is no need to raise the alkalinity of the slurry to above pH 12, thereby avoiding a series of problems caused by high-alkali processes, such as foam viscosity, pipe scaling, and high tailwater treatment load. Attached Figure Description

[0033] The accompanying drawings, which are included to provide a further understanding of embodiments of the invention and form part of this application, do not constitute a limitation thereof. In the drawings:

[0034] Figure 1 This is a flowchart of the overall process flow of the copper-arsenic flotation separation method of the present invention.

[0035] Figure 2 This is a comparison chart of arsenic grade and copper recovery rate in copper concentrate of the present invention and the control reagent system.

[0036] Figure 3A comparison chart of arsenic grade and copper recovery in copper concentrate with missing components.

[0037] Figure 4 The graph shows the flotation recovery rate of four single minerals as a function of pulp pH after the addition of the arsenic inhibitor composition of the present invention.

[0038] Figure 5 The graph shows the flotation recovery rate of four single minerals as a function of pulp pH after the addition of mercaptoacetic acid.

[0039] Figure 6 The graph shows the effect of the dosage of the arsenic inhibitor composition on the arsenic grade and copper recovery rate of the crude concentrate.

[0040] Figure 7 This is a graph showing the effect of pulp pH on the arsenic grade and copper recovery rate of the rough and concentrate.

[0041] Figure 8 The graph shows the effect of the weight ratio of sulfite to oxidation inducer on the pulp potential and copper recovery rate.

[0042] Figure 9 The adsorption isotherms of multifunctional polymeric inhibitors on the surfaces of four minerals are shown.

[0043] Figure 10 A comparison diagram of the surface contact angles of four minerals under different reagent regimes.

[0044] Figure 11 The graph shows the effect of the amount of oxidation inducer on the proportion of high valence states on the surface of arsenopyrite and the amount of inhibitor adsorbed.

[0045] Figure 12 This is a graph showing the evolution of slurry potential with stirring activation time under different reagent regimes. Detailed Implementation

[0046] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0047] It should be noted that the arsenic-bearing copper ore mentioned in this article refers to ore containing both copper sulfide minerals and arsenic-bearing minerals, and whose arsenic content in the copper concentrate obtained under conventional flotation processes exceeds the smelting requirements. The copper sulfide minerals include, but are not limited to, chalcopyrite, chalcocite, bornite, and covellite; the arsenic-bearing minerals include, but are not limited to, arsenopyrite, arsenic chalcopyrite, arsenic sulfide, realgar, and orpiment. The multifunctional polymer inhibitors mentioned in this article refer to water-soluble polymers with carboxyl, mercapto, and phenolic hydroxyl groups on the same molecular chain. Their backbone source is unrestricted and can be modified products of natural polyphenols or grafted products of synthetic polycarboxylic acids. The oxidation inducers mentioned in this article refer to inorganic oxidizing salts that can release active oxygen or participate in cathodic reduction in the form of high-valence anions in moderately alkaline slurries, thereby inducing the formation of oxygen-containing active sites on the surface of arsenic-bearing minerals. Their role in this invention is not to oxidize and decompose the arsenic-bearing minerals as a whole, but only to induce sites on their surface for the inhibitor to anchor; hence, they are called inducers rather than oxidants. Unless otherwise specified, the slurry potentials mentioned in this article refer to the potential values ​​relative to the standard hydrogen electrode. Unless otherwise stated, all percentages mentioned in this article refer to weight percentages for formulation composition and mass percentages for mineral grade and recovery rate.

[0048] It should be noted that the arsenic grade and copper recovery rate of the copper concentrate used in the following examples are based on the final copper concentrate index after three rounds of cleaning in the closed-circuit test, and the rough concentrate index after one round of roughing in the single-factor test. The two values ​​are not on the same benchmark and are not compared across tables.

[0049] Example 1

[0050] This embodiment discloses the preparation of a multifunctional polymer inhibitor (Preparation Example A, brand name GS201-A).

[0051] In this embodiment, to obtain a polymeric inhibitor with carboxyl, thiol, and phenolic hydroxyl groups on the same molecular chain, and a number-average molecular weight in the range of 5000-20000, a two-step modification route was adopted, using natural polyphenols as the backbone and sequentially introducing carboxyl and thiol groups. The reason for choosing natural polyphenols as the backbone is that their molecules are already rich in phenolic hydroxyl groups, eliminating the need for additional introduction to meet the phenolic hydroxyl content requirements. Furthermore, they possess the green attributes of readily available raw materials, biodegradability, and no introduction of heavy metals or cyanide groups.

[0052] This embodiment includes the following steps:

[0053] Step 1: Chain extension of the skeletal framework. Dissolve 100 parts by weight of tannic acid in 400 parts by weight of deionized water, adjust the pH of the system to 10.5 with sodium hydroxide solution, and slowly add 4-8 parts by weight of epichlorohydrin at 60°C. After the addition is complete, keep the reaction at the temperature for 2 hours to obtain the chain-extended polyphenol skeletal solution.

[0054] Epichlorohydrin acts as a bifunctional chain extender, with its epoxy and chloromethyl groups reacting with phenolic hydroxyl groups on different molecules to undergo etherification reactions, thereby increasing the molecular weight of tannic acid from approximately 1700 to the target range. Understandably, the amount of chain extender used must be strictly controlled between 4 and 8 parts by weight: too low a amount results in insufficient molecular weight increase, and the chain length is insufficient to cross two adjacent adsorption sites on the mineral surface, making it impossible to form a polydentate conformation; too high a amount leads to excessive cross-linking and gelation of the system, causing the product to lose its water solubility.

[0055] Step 2: Introduce carboxyl groups. Cool the above solution to 45°C, adjust the pH to 8.0, and add 25-40 parts by weight of maleic anhydride in batches, maintaining the pH at 7.5-8.5. React for 1.5 hours to allow the anhydride to undergo esterification and ring-opening with some of the phenolic hydroxyl groups, thus attaching carboxyl groups to the molecular chain.

[0056] Step 3: Introduce thiol groups. Add 8-15 parts by weight of mercaptoacetic acid and 1 part by weight of p-toluenesulfonic acid, heat to 70°C, and esterify under nitrogen protection for 3 hours, attaching the thiol groups to the remaining hydroxyl positions via ester bonds. The purpose of nitrogen protection is to prevent the thiol groups from being oxidized to disulfide bonds and deactivated by air at the reaction temperature.

[0057] Step 4: Neutralization and drying. After the reaction is complete, cool to 40℃, neutralize with sodium hydroxide solution to pH 7.5~8.5, and spray dry to obtain the multifunctional polymer inhibitor, denoted as GS201-A.

[0058] Characterization showed that the product of this embodiment had a number average molecular weight of 8600, a carboxyl content of 3.8 mmol / g, a thiol content of 0.82 mmol / g, a phenolic hydroxyl content of 1.6 mmol / g, and a phenolic hydroxyl retention rate of 58%.

[0059] Understandably, the content of the three types of functional groups must fall within their respective ranges simultaneously. The carboxyl and phenolic hydroxyl groups jointly undertake ortho-position chelation of trivalent iron sites, and their content determines the density of the chelating teeth; the thiol group undertakes soft-soft coordination of arsenic and monovalent copper sites, and its content has a clear upper limit constraint—when the thiol content is too high, the polymer chain can achieve multi-point anchoring even on the surface of copper minerals lacking iron sites by relying on dense thiol groups, and the selectivity will break down. This is why small molecule thiol agents such as mercaptoacetic acid (with a thiol content as high as about 10.9 mmol / g) inhibit chalcocite while inhibiting arsenopyrite.

[0060] Example 2

[0061] This embodiment discloses the preparation of a multifunctional polymer inhibitor (Preparation Example B, grade GS201-B).

[0062] In this embodiment, in order to examine the applicability of the skeleton source to the present invention, an amidation route was adopted, which uses synthetic polycarboxylic acid as the skeleton and sequentially grafts mercapto-containing and phenolic hydroxyl-containing units.

[0063] This embodiment includes the following steps:

[0064] Step 1: Take 100 parts by weight of polyacrylic acid with a number average molecular weight of approximately 12,000, dissolve it in 500 parts by weight of deionized water, and adjust the pH to 5.5.

[0065] Step 2: Add 12 parts by weight of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 6 parts by weight of N-hydroxysuccinimide to activate the carboxyl group for 30 minutes.

[0066] Step 3: Add 9 parts by weight of L-cysteine ​​and react at 30°C for 4 hours under nitrogen protection. The thiol group is introduced by the formation of an amide bond between the amino group and the activated carboxyl group.

[0067] Step 4: Add 14 parts by weight of p-aminophenol and react at 35°C for 4 hours to introduce phenolic hydroxyl groups; then neutralize with sodium hydroxide to pH 8.0, dialyze to remove small molecules and freeze dry to obtain a multifunctional polymer inhibitor, denoted as GS201-B.

[0068] Characterization showed that the product of this embodiment had a number average molecular weight of 13,500, a carboxyl content of 5.2 mmol / g, a thiol content of 0.61 mmol / g, and a phenolic hydroxyl content of 0.94 mmol / g.

[0069] It should be noted that the skeleton sources, bonding modes, and functional group distributions of Examples 1 and 2 are different. However, as long as the content and number-average molecular weight of the three types of functional groups fall within the range defined by this invention, the arsenic inhibition selectivity shown by the two examples in subsequent applications is substantially different. This indicates that the technical effect of this invention is determined by the functional group composition and molecular weight, rather than by a specific synthetic route. Therefore, the multifunctional polymer inhibitors described in this invention should not be construed as being limited to the products of the two routes mentioned above.

[0070] Example 3

[0071] This embodiment discloses a selective arsenic inhibitor composition.

[0072] Weigh out the following components by weight: 40 parts of the multifunctional polymer inhibitor GS201-A obtained in Example 1, 30 parts of sodium sulfite, 10 parts of sodium persulfate, and 8 parts of water glass. Mix the above solid materials evenly at room temperature to obtain the selective arsenic inhibitor composition of the present invention, denoted as Z1. The weight ratio of sulfite to oxidation inducer is 3:1.

[0073] Example 4

[0074] This embodiment discloses a selective arsenic inhibitor composition.

[0075] Weigh out the following components by weight: 35 parts of the multifunctional polymer inhibitor GS201-B obtained in Example 2, 35 parts of sodium metabisulfite, 12 parts of sodium percarbonate, and 6 parts of sodium hexametaphosphate. Mix them evenly to obtain composition Z2. The weight ratio of sulfite to oxidation inducer is approximately 2.9:1.

[0076] Example 5

[0077] This embodiment discloses a selective arsenic inhibitor composition.

[0078] Weigh out the following components by weight: 30 parts GS201-A, 20 parts sodium sulfite, 5 parts potassium permanganate, and 5 parts water glass. Mix them thoroughly to obtain composition Z3. The weight ratio of sulfite to oxidation inducer is 4:1.

[0079] Example 6

[0080] This embodiment discloses a selective arsenic inhibitor composition.

[0081] Weigh out the following components by weight: 50 parts GS201-B, 40 parts sodium metabisulfite, 15 parts ammonium persulfate, and 10 parts sodium hexametaphosphate. Mix them thoroughly to obtain composition Z4. The weight ratio of sulfite to oxidation inducer is approximately 2.7:1.

[0082] Example 7

[0083] This embodiment discloses a selective arsenic inhibitor composition that does not contain a dispersant.

[0084] Weigh out the following components by weight: 40 parts GS201-A, 30 parts sodium sulfite, and 10 parts sodium persulfate. Mix them thoroughly to obtain composition Z5. This example illustrates that, without a dispersant, the composition consisting of a multifunctional polymeric inhibitor, sulfite, and oxidation inducer can achieve the core technical effect of this invention. The role of the dispersant is to further improve the yield of the agent on the surface of the mineral particles.

[0085] It should be noted that the oxidation inducer and sulfite in the above compositions are oxidizing agents and reducing agents to each other. Although the reaction rate is extremely low in the dry state, it is advisable to prepare and use them immediately in order to avoid mutual consumption during long-term storage. Alternatively, the two can be packaged separately and added to the slurry at the same time in step c, which has the same effect as the premix.

[0086] Application Example 1

[0087] This application example uses composition Z1 prepared in Example 3 to conduct a flotation test on an arsenic-containing copper ore (denoted as ore sample A). The main metallic minerals in ore sample A are chalcopyrite, chalcocite, arsenopyrite, and arsenopyrite. The raw ore contains 0.48% Cu and 0.019% As. The process flow is as follows: Figure 1 As shown, a closed-loop process consisting of one coarse selection, two sweep selections, and three fine selections is employed. This application example includes the following steps:

[0088] Step a: Grind ore sample A to -200 mesh (80%) and prepare a slurry with a mass concentration of 33%.

[0089] Step b: Adjust the pH of the slurry to 10.0 with lime.

[0090] Step c: Add composition Z1400g / t to the roughing process and stir for 5 minutes for activation. Online monitoring showed that the slurry potential stabilized at +214~+221mV within 2~8 minutes of activation.

[0091] Step d: Add 60g / t of collector 2025A, 20g / t of butyl xanthate, and 40g / t of frother 2# oil for flotation. The amount of reagents used in scavenging and cleaning operations decreases sequentially.

[0092] The final copper concentrate obtained had a Cu grade of 20.15%, a Cu recovery rate of 88.62%, and an As grade of 0.41%.

[0093] Application Example 2

[0094] Except for replacing the composition with the dispersant-free composition Z5 obtained in Example 7, and maintaining the dosage at 400 g / t, all other conditions were exactly the same as in Application Example 1. The final copper concentrate obtained had a Cu grade of 19.96%, a Cu recovery rate of 87.84%, and an As grade of 0.45%.

[0095] Application Example 3

[0096] This application example examines the applicability of the present invention to ores with arsenopyrite as the main arsenic-bearing mineral. The ore sample used is designated as ore sample B, whose main metallic minerals are chalcopyrite, arsenopyrite, and a small amount of pyrite. The raw ore contains 1.15% Cu and 0.31% As. The grinding fineness is -200 mesh, accounting for 78%. The pH of the slurry is adjusted to 10.5 with lime, and the composition Z2500g / t obtained in Example 4 is added. The mixture is stirred and activated for 6 minutes. The remaining reagent preparation and process are the same as in Application Example 1.

[0097] The final copper concentrate obtained had a Cu grade of 22.40%, a Cu recovery rate of 87.05%, and an As grade of 0.38%.

[0098] Comparative Example 1

[0099] The ore sample used in this comparative example is from the same batch as that in Application Example 1. The process flow and reagent dosage are exactly the same as in Application Example 1, except that the inhibitor is replaced with an equal amount of sodium sulfite.

[0100] The final copper concentrate obtained had a Cu grade of 19.27%, a Cu recovery rate of 86.15%, and an As grade of 0.55%.

[0101] Comparative Example 2

[0102] The ore sample used in this comparative example was from the same batch as that in Application Example 1. The process flow and reagent dosage were exactly the same as in Application Example 1, except that the inhibitor was replaced with an equal amount of mercaptoacetic acid.

[0103] The final copper concentrate obtained had a Cu grade of 18.91%, a Cu recovery rate of 80.43%, and an As grade of 0.49%.

[0104] Comparative Example 3

[0105] This comparative example is a blank test, and the ore sample used is from the same batch as that in Application Example 1. The process flow and other reagent regimes are exactly the same as in Application Example 1, but no inhibitors are added.

[0106] The final copper concentrate obtained had a Cu grade of 17.85%, a Cu recovery rate of 90.30%, and an As grade of 0.72%.

[0107] Based on Comparative Example 3, it can be seen that Application Example 1 reduced the arsenic grade of copper concentrate from 0.72% to 0.41%, a relative decrease of 43.1%; at the same time, the copper recovery rate only decreased from 90.30% to 88.62%, an absolute loss of 1.68 percentage points and a relative loss of 1.86%; while the copper concentrate grade increased from 17.85% to 20.15%.

[0108] This set of data also confirms the technical effect of the present invention, which reduces arsenic by more than 40% while the copper recovery rate loss is no more than 2%. The copper grade increases instead of decreasing because, within the potential window controlled by the present invention, the chalcopyrite surface undergoes shallow oxidation to form a sulfur-rich defect layer, which slightly enhances its hydrophobicity, thereby further enriching the arsenic-containing minerals while suppressing them.

[0109] from Figure 2 As can be seen, compared with the blank test without inhibitors, the composition of the present invention reduces the arsenic grade of copper concentrate by 43.06%, while the relative loss of copper recovery is only 1.86%. In other words, the present invention can significantly remove arsenic without sacrificing copper recovery.

[0110] Comparative Example 4

[0111] The ore sample used in this comparative example is from the same batch as that in Application Example 1. The process flow, total reagent dosage (400g / t), and other conditions are the same. However, the composition used consists of 40 parts of GS201-A, 30 parts of sodium sulfite, and 8 parts of water glass, and does not contain an oxidation inducer.

[0112] The final copper concentrate obtained had a Cu grade of 19.42%, a Cu recovery rate of 87.95%, and an As grade of 0.53%.

[0113] Comparative Example 5

[0114] The ore sample used in this comparative example is from the same batch as that in Application Example 1. The process flow, total reagent dosage and other conditions are the same, but the composition used consists of 40 parts of GS201-A, 10 parts of sodium persulfate and 8 parts of water glass, and does not contain sulfites.

[0115] The final copper concentrate obtained had a Cu grade of 19.88%, a Cu recovery rate of 83.71%, and an As grade of 0.44%. Online monitoring showed that the slurry potential in this comparative example continuously rose from +322mV to +412mV within 2-8 minutes of stirring and activation, remaining outside the upper limit of the potential window throughout the process.

[0116] Comparative Example 6

[0117] The ore sample used in this comparative example is from the same batch as that in Application Example 1. The process flow, total reagent dosage and other conditions are the same. However, the composition used consists of 30 parts sodium sulfite, 10 parts sodium persulfate and 8 parts water glass, and does not contain polyfunctional polymer inhibitors.

[0118] The final copper concentrate obtained had a Cu grade of 18.76%, a Cu recovery rate of 88.05%, and an As grade of 0.63%.

[0119] Comparative Example 7

[0120] The ore sample used in this comparative example is from the same batch as that in Application Example 1. The process flow, total reagent dosage, and other conditions are the same. However, 40 parts of the multifunctional polymer inhibitor were replaced with a mixture of three small molecule reagents that provide equal amounts of functional groups, namely a mixture of sodium acetate, mercaptoacetic acid, and catechol. The other components remain unchanged.

[0121] The final copper concentrate obtained had a Cu grade of 19.05%, a Cu recovery rate of 82.60%, and an As grade of 0.52%.

[0122] Comparative Example 8

[0123] The ore sample used in this comparative example is from the same batch as that in Application Example 3 (ore sample B). The composition of this invention is not added; instead, lime is used to raise the slurry pH to 12.3, with a lime dosage of 5200 g / t. The remaining reagent preparation and procedures are the same as in Application Example 3.

[0124] The final copper concentrate obtained had a Cu grade of 21.16%, a Cu recovery rate of 85.30%, and an As grade of 0.86%. During the experiment, the foam was noticeably viscous and difficult to scrape off, and the foam entrainment was severe during the beneficiation process.

[0125] Summary of comparative test results:

[0126] The closed-circuit test results for each example of mineral sample A are summarized in Table 1.

[0127] Table 1 Results of Closed-Circuit Flotation Tests for Mineral Sample A

[0128]

[0129] The arsenic reduction and copper recovery rate loss in the table are calculated based on the blank test of Comparative Example 3; Composition Z1 is the full formulation obtained in Example 3, and Composition Z5 is the formulation without dispersant obtained in Example 7.

[0130] Understandably, the most telling aspect of Table 1 is not the individual comparison between Application Example 1 and any of the comparative examples, but rather the fact that Application Example 1 outperforms all the comparative examples simultaneously in both arsenic grade and copper recovery. In the conventional behavior of flotation depressants, there is a monotonic trade-off between arsenic grade and copper recovery: increased depressant action leads to decreased arsenic and decreased copper, while decreased depressant action leads to increased copper and increased arsenic. Therefore, simply adjusting the dosage of any existing depressant cannot simultaneously achieve both indicators of Application Example 1 on the same trade-off curve. Comparative Example 5 particularly illustrates this point: its arsenic grade of 0.44% is close to that of Application Example 1 (0.41%), but its copper recovery is 4.91 percentage points lower. In contrast, Application Example 1, compared to Comparative Example 5, only added sulfite, yet simultaneously further reduced arsenic while increasing copper recovery by nearly 5 percentage points. This means that the system is not undergoing a quantitative change in depressant strength, but a qualitative change in selectivity; that is, the interaction between the three components is a synergistic coupling rather than a simple addition.

[0131] from Figure 3 As can be seen, the full formulation is superior to the control group (excluding all single components) in both the arsenic grade and copper recovery rate of copper concentrate. Compared with the control group (excluding sulfites), the full formulation has a copper recovery rate that is 4.91 percentage points higher, while the arsenic grade is lower.

[0132] It should be noted that the comparison of Examples 4, 5, and 6 further reveals the irreplaceable roles of each component: after removing the oxidation inducer, the arsenic grade increased significantly from 0.41% to 0.53%, while the copper recovery rate remained basically unchanged, indicating that the function of the oxidation inducer is to suppress arsenic (provide adsorption sites); after removing sulfite, the arsenic grade only increased slightly to 0.44%, but the copper recovery rate plummeted by 4.91 percentage points, and the pulp potential remained outside the upper limit of the window throughout, indicating that the function of sulfite is to retain copper (clamp the potential within the window); after removing the polymeric inhibitor, the arsenic grade increased to 0.63%, close to the blank level, indicating that the polymeric inhibitor is the main body for forming the hydrophilic film, and the former two do not have the ability to suppress arsenic. The functions of the three components do not overlap, so the absence of any one cannot be compensated for by the other components.

[0133] Comparative Example 7 illustrates that dispersing the three types of functional groups on three different small molecules cannot replace concentrating them on the same polymer chain: its arsenic content is only 0.52%, and the copper recovery rate drops to 82.60% due to the introduction of a high content of free thiol groups. This is consistent with the multidentate anchoring mechanism of this invention, that is, only when the three types of functional groups are located on the same chain can they simultaneously form bonds at adjacent sites on the surface of arsenic-containing minerals, amplifying the free energy advantage of monodentate adsorption exponentially according to the number of teeth; while when dispersed on different molecules, each can only perform monodentate adsorption, and the selectivity factor approaches 1.

[0134] The test results of mineral sample B are summarized in Table 2.

[0135] Table 2 Results of Closed-Circuit Flotation Tests for Mineral Sample B

[0136]

[0137] As shown in Table 2, for mineral sample B, where arsenopyrite is the main arsenic mineral, the lime-high-alkali method has almost no effect on arsenic suppression, with the arsenic grade in the copper concentrate reaching as high as 0.86%. However, the composition of this invention, under moderately alkaline conditions at pH 10.5, suppresses the arsenic grade to 0.38%, while simultaneously achieving higher copper recovery and grade than the lime-high-alkali method, without exhibiting foaming or viscous phenomena. This is because arsenopyrite itself is a copper-bearing mineral, and its floatability is highly similar to that of chalcopyrite; simply increasing alkalinity cannot differentiate between the two. This invention relies on the difference in the completeness of arsenic and copper sites, which is unrelated to alkalinity, thus making it equally effective for arsenopyrite.

[0138] Experimental Example 1

[0139] This experimental example illustrates the effect of pulp pH.

[0140] Using ore sample A as the object, a roughing open-circuit test was conducted under the conditions of grinding fineness of -200 mesh accounting for 80%, composition Z1 dosage of 400 g / t, and stirring and activation for 5 minutes, and the pH of the slurry was changed. The results are shown in Table 3.

[0141] Table 3. Effects of pulp pH on roughing parameters

[0142]

[0143] Understandably, the arsenic suppression effect is significantly insufficient at pH levels below 8.5 for two reasons: first, the hydroxylation sites on the surface of ferric iron are unstable below weak alkalinity, and the site density decreases with decreasing pH; second, the thiol groups undergo protonation on the acidic side, losing their coordination ability. At pH levels above 11.0, the copper recovery rate begins to decline significantly because a hydrophilic copper hydroxyl compound film begins to form on the surface of copper minerals, and the polymer chains overextend under high charge density, limiting the effective adsorption conformation. Therefore, this invention limits the slurry pH to 8.5–11.0, with 9.0–11.0 being preferred.

[0144] from Figure 7 As can be seen, within the pH range of 8.5 to 11.0, the arsenic grade of the crude concentrate is no higher than 0.55% and the copper recovery rate is no lower than 91.5%. However, at pH 7.0, the arsenic grade rises to 0.78%, and at pH 12.0, the copper recovery rate drops to 87.2%. In other words, the effective window of this scheme does indeed fall within the medium-alkaline range, and there is no need to raise the slurry alkalinity to a high-alkaline level.

[0145] Experimental Example 2

[0146] This experimental example illustrates the effect of the amount of the composition used.

[0147] Under the same conditions as in Experiment 1, with the pH fixed at 10.0, the amount of composition Z1 was varied, and the results are shown in Table 4.

[0148] Table 4. Effect of Composition Dosage on Rough Selection Indicators

[0149]

[0150] It should be noted that after the dosage exceeds 600 g / t, the further decrease in arsenic grade is less than 0.01 percentage points, while the copper recovery rate drops sharply by 3.3 percentage points in the 600-800 g / t range. This is consistent with the inference of the multidentate adsorption model: when the reagent concentration is high enough, the monodentate adsorption on the copper mineral surface will accumulate to a level sufficient to cover the collector's coverage, and the selectivity will narrow again. Therefore, the dosage of the composition in this invention is limited to 200-600 g / t.

[0151] from Figure 6As can be seen, when the dosage increased from 600g / t to 800g / t, the arsenic grade of the crude concentrate only continued to decrease by 0.01 percentage points, while the copper recovery rate decreased by 3.3 percentage points. This confirms that there is a clear upper limit to the dosage in this scheme, and the selectivity is narrowed again after exceeding this upper limit.

[0152] Experimental Example 3

[0153] The conditions were the same as in Experiment 2, with a fixed total dosage of 400 g / t, pH 10.0, and fixed proportions of multifunctional polymer inhibitor and dispersant. Only the weight ratio of sulfite to oxidation inducer was changed, and the slurry potential at the end of 5 minutes of stirring activation was measured online using a platinum electrode. The results are shown in Table 5.

[0154] Table 5 Effect of the weight ratio of sulfite to oxidation inducer

[0155]

[0156] For example, in this embodiment, the potential data in Table 5 can be quantitatively verified as follows: In the range of 2:1 to 12:1, for every order of magnitude change in weight ratio, the slurry potential changes by only about 98 mV, which is consistent with the expected magnitude of buffer control in the mixed potential model, indicating that the system in this range is indeed dominated by redox buffer pairs; while in the range of 0.5:1 to 2:1, the potential change corresponding to the same logarithmic change increases sharply to about 171 mV / decade, indicating that the reserves of reducing components are insufficient to maintain buffer, the system is out of buffer control, the slurry potential rises with reagent consumption and oxygen consumption and crosses the upper limit of the window +250 mV, chalcocite thus undergoes deep oxidation, and the copper recovery rate drops to below 85.9%.

[0157] from Figure 8 As can be seen, when the weight ratio of sulfite to oxidation inducer is in the range of 2:1 to 6:1, the pulp potential falls between 191.0 and 238.0 mV, which is within the +50 to +250 mV window, and the copper recovery rate is not less than 91.3%. However, when the weight ratio drops to 1:1, the pulp potential rises to 289.0 mV, exceeding the upper limit of the window, and the copper recovery rate drops to 85.9%.

[0158] On the other hand, when the weight ratio is higher than 6:1, although the slurry potential still falls within the window, the absolute amount of oxidation inducer has decreased to an insufficient density of sites to induce on the surface of arsenic-bearing minerals, and the arsenic grade deteriorates from 0.48% to 0.63%. It is understandable that the weight ratio parameter simultaneously constrains two things—the potential landing point and the site supply. The intersection of the feasible ranges of the two yields the 2:1 to 6:1 range defined in this invention.

[0159] Test Example 4

[0160] The conditions were the same as in Experiment 3, with a fixed weight ratio of 3:1, but the stirring and activation time was varied. The results are shown in Table 6.

[0161] Table 6. Effect of stirring activation time

[0162]

[0163] The arsenic inhibition effect showed a single-peak shape, first increasing and then decreasing with activation time, with a plateau region between 2 and 8 minutes. This can be understood as the result of the combined effect of two competing processes: site formation and the exfoliation of the oxidation product layer. When the activation time is insufficient, sites are not fully formed; when the activation time is too long, the oxidation inducer has been exhausted by sulfites and the mineral surface, the site formation term approaches zero, while the exfoliation term continues to act, and the surface oxidation product layer, along with the inhibitors adsorbed on it, is detached, causing the arsenic inhibition effect to decline.

[0164] Experimental Example 5

[0165] This experimental example illustrates the effect of grinding fineness.

[0166] The conditions were the same as in Experiment 4, with a fixed activation time of 5 minutes, but the grinding fineness was varied. The results are shown in Table 7.

[0167] Table 7. Effect of Grinding Fineness

[0168]

[0169] When the fineness is below -200 mesh (70%), the arsenic-containing minerals are not sufficiently liberated, and the intergrowths float to the surface along with the copper minerals. When the fineness is above -200 mesh (85%), the amount of newly formed slime exceeds the dispersing capacity of the dispersant, and the slime covering reduces the effectiveness of the reagent on the surface of the mineral particles, resulting in a simultaneous deterioration of both indicators. Therefore, this invention limits the grinding fineness to 70%~85% -200 mesh.

[0170] Experimental Example 6: Effect of Number-Average Molecular Weight

[0171] Following the route of Example 1, a series of multifunctional polymer inhibitors with different number average molecular weights were prepared by adjusting the amount of epichlorohydrin in step 1, while keeping the content of other functional groups at the same level. A rough selection test was conducted under the conditions of Experimental Example 5 (fineness -200 mesh accounts for 80%), and the results are shown in Table 8.

[0172] Table 8. Effect of Number-Average Molecular Weight

[0173]

[0174] When the molecular weight is below 5000, the extension length of the molecular chain is insufficient to cross adjacent iron and arsenic sites on the surface of arsenic-containing minerals, preventing the formation of a polydentate conformation. The inhibitory effect degenerates into monodentate adsorption, significantly reducing the arsenic suppression effect. When the molecular weight is above 20000, the polymer chains coil up in solution, reducing the accessibility of internal functional groups. Simultaneously, the cross-particle bridging effect of the chains is enhanced, leading to non-selective flocculation of copper minerals and their inclusion in tailings, resulting in a significant decrease in copper recovery. Therefore, this invention limits the number-average molecular weight to 5000-20000.

[0175] Experimental Example 7

[0176] Single minerals of arsenopyrite, chalcopyrite, lapis lazuli, and chalcocite with a purity greater than 95% were ground to -74 ± 38 μm and subjected to single-mineral flotation tests in a hanging flotation machine using 40 mg / L composition Z1 as a depressant, 60 mg / L butyl xanthate as a collector, and 20 mg / L No. 2 oil as a frother, with the pulp pH varied. The results are shown in Table 9. As a control, the above tests were repeated using the same concentration of mercaptoacetic acid instead of composition Z1, and the results are shown in Table 10.

[0177] Table 9. Flotation recovery rates (%) of four single minerals after adding the composition of the present invention.

[0178]

[0179] Table 10. Flotation recoveries (%) of four single minerals after the addition of mercaptoacetic acid

[0180]

[0181] Understandably, single-mineral tests eliminate interfering factors such as intergrowth, capping, and reagent competition in the ore, directly reflecting the selectivity of the inhibitor itself. Within the pH range of 9.0–11.0, after adding the composition of this invention, the lowest recovery rate among the two copper minerals remained more than 60 percentage points lower than the highest recovery rate among the two arsenic-containing minerals. Furthermore, after adding mercaptoacetic acid, the recovery rate of chalcocite was even lower than that of arsenopyrite, with a negative difference, indicating that under these conditions, mercaptoacetic acid inhibited chalcocite more strongly than arsenopyrite, making copper-arsenic separation theoretically impossible. This comparison provides direct evidence of the selective advantage of this invention over small-molecule thiol inhibitors.

[0182] from Figure 4 As can be seen, within the pH range of 9.0–11.0, the difference between the lowest recovery rate of the two copper minerals and the highest recovery rate of the two arsenic-containing minerals consistently remained above 63.0 percentage points. From... Figure 5It can be seen that under the same conditions, the separation interval corresponding to mercaptoacetic acid is always negative in the pH range of 9.0~11.0, with a maximum value of only -4.0 percentage points, that is, the degree of inhibition of chalcocite is stronger than that of arsenic chalcocite.

[0183] Experiment 8

[0184] Under the conditions of pH 10.0 and 25℃, the above four single mineral powders were placed in solutions of multifunctional polymer inhibitors with different initial concentrations and shaken for 2 hours until adsorption equilibrium was reached. The concentration of residual reagent in the solution was determined by the total organic carbon method, and the adsorption amount on the mineral surface was calculated by the difference method. The results are shown in Table 11.

[0185] Table 11. Equilibrium adsorption capacity (mg / g) of multifunctional polymeric inhibitors on the surfaces of four minerals.

[0186]

[0187] All four isotherms conform to Langmuir-type adsorption characteristics. At an equilibrium concentration of 40 mg / L, the adsorption amount of the inhibitor on the surface of arsenopyrite is approximately 9 times that on the surface of chalcocite, and the adsorption amount on the surface of arsenic tetrahedrite is approximately 4.9 times that on the surface of chalcopyrite. Understandably, the huge difference in adsorption amount stems from the difference in the number of adsorption teeth: after oxidation induction, the surface of arsenopyrite possesses three types of anchor sites simultaneously: trivalent iron hydroxyl sites, arsenic oxygen sites, and residual soft acid sites, allowing the inhibitor to form tridentate adsorption; while the surface of copper minerals only has one type of usable anchor site, allowing only monodentate adsorption. Its adsorption free energy is much smaller than that of the former, and when amplified according to the exponential relationship of the selectivity factor, this manifests as an order-of-magnitude difference in adsorption amount.

[0188] from Figure 9 As can be seen, at an equilibrium concentration of 40 mg / L, the adsorption amount of the inhibitor on the surface of arsenopyrite is 8.92 times that on the surface of chalcocite, and the adsorption amount on the surface of arsenic chalcopyrite is 4.91 times that on the surface of chalcopyrite. This confirms that multi-toothed anchoring amplifies the difference in site completeness into an order-of-magnitude difference in adsorption amount.

[0189] Experimental Example 9

[0190] Polished discs of the above four single minerals were taken and their surface contact angles were measured under three reagent regimes at pH 10.0. The results are shown in Table 12.

[0191] Table 12 Surface contact angles of four minerals under different reagent regimes.

[0192]

[0193] Compared to the case where only the collector is added, after adding the composition of the present invention, the surface contact angles of arsenopyrite and chalcocite decreased by 47°, and the surfaces changed from hydrophobic to strongly hydrophilic, indicating that the inhibitor had formed a continuous hydrophilic film on their surfaces; while the contact angles of chalcopyrite and chalcocite only decreased by 4° and 5°, respectively, and remained at a strongly hydrophobic level of over 74°, indicating that the inhibitor failed to form an effective coating on the copper mineral surface.

[0194] from Figure 10 As can be seen, after adding the composition of the present invention, the surface contact angle of the two arsenic-containing minerals decreased by at least 47.0 degrees compared with the case where only the collector was added, while the decrease of the two copper minerals was only 5.0 degrees at most, which proves that the inhibitor only formed a continuous hydrophilic film on the surface of the arsenic-containing minerals and did not cover the surface of the copper minerals.

[0195] Experimental Example 10: Surface Valence State and Pulp Potential Evolution

[0196] Arsene mineral was taken and the amount of oxidation inducer was varied under the conditions of pH 10.0 and a fixed weight ratio of sulfite to oxidation inducer of 3:1. After 5 minutes of treatment, the mineral was taken out, washed in an oxygen-free environment and dried under vacuum. The relative proportion of high-valence components in Fe2p and As3d spectra on the surface was determined by X-ray photoelectron spectroscopy. At the same time, the amount of inhibitor adsorbed on the surface of arsene under the same conditions was determined. The results are shown in Table 13.

[0197] Table 13 Effect of oxidation inducer dosage on the surface valence state and inhibitor adsorption capacity of arsenopyrite

[0198]

[0199] When the dosage of the oxidation inducer increased from 0 to 40 g / t, the proportion of trivalent iron on the surface of arsenopyrite increased from 18% to 68%, the proportion of high-valence arsenic increased from 12% to 63%, and the adsorption capacity of the inhibitor increased from 0.9 mg / g to 3.4 mg / g, showing a synchronous increase. This directly confirms the mechanism of action of the oxidation inducer—it does not directly inhibit arsenic-containing minerals, but rather creates conditions for the anchoring of the inhibitor by inducing the formation of high-valence oxygen-containing sites on their surface; after the dosage exceeds 40 g / t, all three curves enter a plateau, indicating that the surface sites have become saturated.

[0200] from Figure 11 As can be seen, when the dosage of oxidation inducer increased from 0 to 40 g / t, the proportion of trivalent iron on the surface of arsenopyrite increased to 3.78 times the original value, and the amount of inhibitor adsorbed also increased to 3.78 times the original value. The two showed a synchronous increase, which proved that the oxidation inducer did not directly inhibit arsenic-containing minerals, but indirectly improved the anchoring ability of the inhibitor by inducing high-valence oxygen-containing sites on its surface.

[0201] Furthermore, under the conditions of pH 10.0 and total reagent dosage of 400 g / t, the evolution of slurry potential with stirring activation time under the three reagent regimes was recorded online using a platinum electrode, and the results are shown in Table 14.

[0202] from Figure 12 As can be seen, within the stirring and activation period of 2 to 8 minutes, the slurry potential corresponding to the composition of the present invention fluctuates only between 214.0 and 221.0 mV, with a bandwidth of only 7.0 mV and always falling within the +50 to +250 mV window; while the control with only oxidation inducer added has a potential of no less than 322.0 mV in the same range, and the control with only sulfite added has a potential of no more than 42.0 mV. Both are outside this window, which confirms that the coexistence of oxidizing and reducing components does indeed buffer the slurry potential, rather than simply canceling each other out.

[0203] Table 14 Evolution of slurry potential with stirring activation time under three reagent regimes (mV)

[0204]

[0205] In summary, the basic implementation scheme in this embodiment is as follows: Sulfite and an oxidation inducer form a redox buffer pair in a moderately alkaline slurry, clamping the slurry potential within a narrow window—above the oxidation initiation potential of arsenic-containing minerals and below the deep oxidation potential of copper minerals. Within this window, the surface of arsenic-containing minerals is directionally oxidized to form a high density of trivalent iron hydroxyl sites and arsenic oxygen sites. This allows the polymeric inhibitors, which simultaneously possess carboxyl, thiol, and phenolic hydroxyl groups, to form a multidentate chelate structure and spread into a continuous hydrophilic film on their surface. However, due to the uneven distribution of sites on the surface of copper minerals, the inhibitors can only form weak monodentate adsorption structures easily replaced by the collector, thus preserving their floatability. The dispersant disperses the sludge to eliminate capping, improving the realization rate of the above three steps on the mineral particle surface. Together, these four components constitute an arsenic inhibitor system that efficiently and selectively inhibits arsenic-containing minerals under moderately alkaline conditions without significantly sacrificing copper recovery.

[0206] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A selective arsenic inhibitor composition for copper-arsenic flotation separation, characterized in that, The selective arsenic inhibitor composition comprises the following components in parts by weight: 30-50 parts of a multifunctional polymer inhibitor, 20-40 parts of sulfite, and 5-15 parts of an oxidation inducer; wherein the multifunctional polymer inhibitor is a water-soluble polymer containing carboxyl, thiol, and phenolic hydroxyl groups on the same molecular chain, and the number average molecular weight of the multifunctional polymer inhibitor is 5000-20000; The weight ratio of the sulfite to the oxidation inducer is 2:1 to 6:

1.

2. The selective arsenic inhibitor composition for copper-arsenic flotation separation according to claim 1, characterized in that, The selective arsenic inhibitor composition also includes 5 to 10 parts by weight of a dispersant.

3. The selective arsenic inhibitor composition for copper-arsenic flotation separation according to claim 1, characterized in that, The multifunctional polymeric inhibitor has a carboxyl group content of 2.0~6.0 mmol / g, a thiol group content of 0.3~1.5 mmol / g, and a phenolic hydroxyl group content of 0.5~3.0 mmol / g.

4. The selective arsenic inhibitor composition for copper-arsenic flotation separation according to claim 1, characterized in that, The sulfite is at least one of sodium sulfite and sodium metabisulfite; The oxidation inducer is at least one of persulfate, percarbonate, and permanganate.

5. The selective arsenic inhibitor composition for copper-arsenic flotation separation according to claim 1, characterized in that, The dispersant is at least one of water glass and sodium hexametaphosphate; The selective arsenic inhibitor composition comprises the multifunctional polymeric inhibitor, the sulfite, the oxidation inducer, and the dispersant; Based on the total weight of the selective arsenic inhibitor composition, the content of the multifunctional polymeric inhibitor is 30%~50%, the content of the sulfite is 20%~40%, the content of the oxidation inducer is 5%~15%, and the content of the dispersant is 5%~10%. Furthermore, the sum of the weight percentages of the above four components is 100%.

6. A method for separating copper and arsenic by flotation, characterized in that, The flotation separation method includes the following steps: a. Grind the arsenic-containing copper ore and prepare it into a slurry; b. Adjust the pH of the slurry to 8.5-11.0; c. Add the selective arsenic inhibitor composition according to any one of claims 1 to 5 to the slurry and stir to activate it, so that the slurry potential of the slurry falls into a set range and a hydrophilic film is formed on the surface of the arsenic-containing minerals in the arsenic-containing copper ore; d. Add a collector and a frother to the slurry treated in step c and perform flotation to obtain copper concentrate and tailings.

7. The selective arsenic inhibitor composition for copper-arsenic flotation separation according to claim 1, characterized in that, In step a, the fineness of the grinding is 70% to 85% -200 mesh; In step b, the pH value of the slurry is 9.0~11.

0.

8. The selective arsenic inhibitor composition for copper-arsenic flotation separation according to claim 1, characterized in that, In step c, The dosage of the selective arsenic inhibitor composition is 200~600g / t; The stirring and activation time is 2-8 minutes; The set range is +50 to +250 mV relative to the standard hydrogen electrode; The sulfite and the oxidation inducer in the selective arsenic inhibitor composition are respectively added to the slurry.

9. The selective arsenic inhibitor composition for copper-arsenic flotation separation according to claim 1, characterized in that, In step d, the collector is at least one of xanthate collectors, nitric acid collectors, and 2025A.

10. The selective arsenic inhibitor composition according to any one of claims 1 to 5, used in the flotation separation of copper minerals and arsenic-containing minerals in arsenic-containing copper ore; The arsenic-containing mineral is at least one of arsenopyrite, arsenic chalcopyrite, and thioarsenic chalcopyrite, and the copper mineral is at least one of chalcopyrite and chalcocite.